Social Media and Post-Relationship Distress Maintenance: A Narrative Analysis Based on Cognitive Behavioral Therapy - Regi Malsya (TheraEdu: Journal of Therapy and Educational Psychology, 2026)
The growing narratives of pain, distrust, and "numbness" post-relationship among young adults, largely reinforced by social media, inspire this research. This qualitative descriptive study aimed to understand factors that perpetuate post-relationship suffering in young adult women using the lens of cognitive behavioral counseling therapy. This research uses a narrative qualitative approach with four female participants aged 18-25 years in Siulak District, Kerinci Regency, who have experienced suffering following a romantic breakup and actively consume emotional content on social media. The data were collected through in-depth interviews and by observing the participants’ digital activity in public content on TikTok and Instagram. The results of the research suggest that discomfort persists via cognitive distortion, social retreat, and emotional reinforcement through the recurrent intake of digital content. The research suggests that social media is not just a location for emotional affirmation but can also preserve a wounded identity. The results suggest the importance of the counseling sincere strategy based on CBT and digital emotional literacy.